Pengembangan Model Intervensi Pekerjaan Sosial Holistik bagi Lansia Terlantar dengan Disorientasi Realitas dan Halusinasi: Bukti dari Studi Kasus Longitudinal di Rumah Perlindungan Sosial Kota Medan - Putri Angel Yosephine Gultom; Gusti Pirandy (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to explore the psychosocial dynamics and effectiveness of social work interventions for neglected elderly individuals with reality disorientation and hallucinations. Using a qualitative approach with a case study design, the research was conducted over 52 days at the Social Protection Home of Medan City involving a 61 year old elderly woman (Mrs. R) who experienced neglect following her husband's death and abandonment by her two sons. Data collection employed in depth interviews, participatory observation, genograms, and eco maps. The intervention integrated Cognitive Behavioral Therapy, Reality Orientation, Validation Therapy, basic needs fulfillment, skin infection treatment, and Christian spiritual guidance. Results showed significant improvements in physical hygiene, healing of skin infections, reduced hallucination frequency, increased communication focus duration, and social adaptation. However, family support systems remained unrecovered due to the sons' total neglect. The study concludes that handling neglected elderly with psychosocial disorders requires a holistic approach and sustainable long term institutional care.